Fracture analysis of thin rotating disc with radial cracks - Eng, Chee Liang (Nanyang Technological University, 2020)
A comparative theoretical investigation using the Boundary Element Method (BEM) and Finite Element Method (FEM) has been performed on a thin rotating disc with slots that are subjected to both radial tangential forces and centrifugal loading. Stress concentration factors (K¬t) and stress intensity factors (KIC) results are obtained and presented during this study. Rotating disc’s geometric parameters were varied to understand the impact of geometry variation on stress concentration and stress intensity factor. The maximum principal stress is observed to develop at the vicinity of 180° in the stress concentration analysis, nearest to the edge of the non-central hole. In this region and its vicinity, the crack is then modelled, and stress intensity factors were obtained. Furthermore, stress concentration factors reduce as the number of non-centric holes or slots rises, ranging from 20 to 40.